Metastatic melanoma of the heart: Retrospective cohort study and systematic review of prevalence, clinical characteristics, and outcomes - Alexander M. Balinski; Alexi L. Vasbinder; Connor C. Kerndt; Tonimarie C. Catalan; Nathan P. Parry; Rafey A. Rehman; Pennelope Blakely; Raymond Y. Yeow; Monika J. Leja; Christopher D. Lao; Leslie A. Fecher; Salim S. Hayek (Cancer Medicine)
Abstract Background Cardiac metastasis of melanoma is rare and typically diagnosed post‐mortem. Here we perform a retrospective cohort study and systematic review of patients with metastatic melanoma to characterize prevalence, clinical characteristics, and outcomes of cardiac metastasis. Methods We reviewed the electronic medical records of all outpatients with metastatic melanoma who underwent evaluation at the University of Michigan in Ann Arbor from January 2009 to January 2022, identifying patients with a clinical or histopathologic diagnosis of cardiac metastasis. We performed a systematic review of the literature to summarize the clinical characteristics and outcomes of patients with melanoma and cardiac metastasis. Results Overall, 23 of 1254 (1.8%) patients with metastatic melanoma were diagnosed with cardiac metastasis. Cardiac metastasis was reported in the right ventricle (65%), left ventricle (35%), and right atrium (35%). A total of 11 (48%) patients experienced at least one cardiovascular complication after the diagnosis of cardiac metastasis, the most common being arrhythmia (30%), heart failure (22%), and pericardial effusion (17%). Immunotherapy was more commonly used in patients with cardiac metastasis (80% vs 65%; p = 0.005). Mortality at 2‐years post‐diagnosis was higher for patients with cardiac metastasis compared to those without (59% vs 37%; p = 0.034). Progression of malignancy was the underlying cause of death of all patients. Conclusions Cardiac metastasis occurs in <2% of patients with metastatic melanoma, can affect all cardiac structures, and is associated with various cardiovascular complications and high mortality.